2017
DOI: 10.1016/j.ensci.2017.04.002
|View full text |Cite
|
Sign up to set email alerts
|

Challenges in diagnosing normal pressure hydrocephalus: Evaluation of the diagnostic guidelines

Abstract: PurposeTo evaluate the present diagnostic guidelines of idiopathic normal pressure hydrocephalus (iNPH) in a sample from the general population.MethodsA total of 168 individuals (93 females, 75 males), mean age 75 years (range 66–92) with and without symptoms of iNPH underwent a CT-scan of the brain, a neurological examination with assessment of the triad symptoms, i.e. gait disturbances, memory impairment and urgency incontinence. The participants were then diagnosed as “unlikely”, “possible” and “probable” i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
35
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
7
2

Relationship

1
8

Authors

Journals

citations
Cited by 39 publications
(35 citation statements)
references
References 30 publications
0
35
0
Order By: Relevance
“…In 2017, Andersson et al 18 evaluated the aforementioned guidelines and found remarkable discrepancies between these and the neurologists. Overall, this paper stated that the Japanese guidelines were more concordant with the professionals, which can be partially explained by the comparative lack of specificity that marks the International Guidelines - neither radiological nor clinical criteria are particular enough, with only one symptom of the classical triad being sufficient for “possible” disease, whereas at least two are necessary according to the Japanese guidelines.…”
Section: Idiopathic Normal-pressure Hydrocephalus (Inph)mentioning
confidence: 99%
See 1 more Smart Citation
“…In 2017, Andersson et al 18 evaluated the aforementioned guidelines and found remarkable discrepancies between these and the neurologists. Overall, this paper stated that the Japanese guidelines were more concordant with the professionals, which can be partially explained by the comparative lack of specificity that marks the International Guidelines - neither radiological nor clinical criteria are particular enough, with only one symptom of the classical triad being sufficient for “possible” disease, whereas at least two are necessary according to the Japanese guidelines.…”
Section: Idiopathic Normal-pressure Hydrocephalus (Inph)mentioning
confidence: 99%
“…Furthermore, this study emphasized the need to review the current guidelines in order to produce a common, more objective, diagnostic system. 18 …”
Section: Idiopathic Normal-pressure Hydrocephalus (Inph)mentioning
confidence: 99%
“…In a recent publication, we compared diagnoses according to the two guidelines and a senior consultant in neurology, respectively. A higher agreement was found between the Japanese guidelines and the neurologist (kappa = 0.69) than between the American-European guidelines and the neurologist (kappa = 0.44) [27]. We concluded that one widely recognized, diagnostic system is needed in order to compare different studies.…”
Section: Discussionmentioning
confidence: 99%
“…Normal pressure hydrocephalus (NPH) is a chronic condition among adults which is characterized by the clinical triad of gait disturbances, memory deficits and urinary incontinence, as well as radiological evidence of ventriculomegaly with disproportionally effaced superior frontal sulci and reduced callosal angle [1]. Despite the fact that it is known that NPH can be secondary to traumatic brain injuries, intracranial hemorrhages and infections, the majority of cases are idiopathic (iNPH), and their pathophysiology remaining puzzling.…”
Section: Introductionmentioning
confidence: 99%